Expediency of Application of the Regional and Municipal (Communal) Wealth Indicators at the Generation of the Regional and Urban Development Strategies - Lyashenko, V.I.; Zhykhareva, Yu.I.; Vyshnevskyy, O.S. (Економічний вісник Донбасу, 2013)
In accord with the analysis of fulfillment of the active regional development strategies in regions of Ukraine the effectiveness of their realization is rather low. There is no correlation between the determined strategic purposes of the regional development. The diversity of targets, which are determined in the strategies, leads to the resource scattering and makes the adequate quality monitoring of these strategies fulfillment impossible. It is impossible to define whether the positive changes took place during the given period in the final conclusion. The analogical situation happens in the process of building the strategy of the local communities' development. Also, the absence of the evaluative composite indicator of the effective realization of the development strategies prevents from the interregional comparison of the social and economic development and the monitoring of the contribution of each region in the national social and economic development.